Eating behaviours in preadolescence are associated with body dissatisfaction and mental disorders – Results of the CCC2000 study. (1st June 2016) - Munkholm, Anja; Olsen, Else Marie; Rask, Charlotte Ulrikka; Clemmensen, Lars; Rimvall, Martin K.; Jeppesen, Pia; Micali, Nadia; Skovgaard, Anne Mette
Abstract: Preadolescence is a key period in the early stages of eating disorder development. The aim of the present study was, firstly, to investigate restrained, emotional and external eating in a general population-based sample of 11–12 year olds. Secondly, we sought to explore how these eating behaviours are associated with possible predictors of eating disorders, such as body dissatisfaction, weight status and mental disorders. A subsample of 1567 children (47.7% boys; 52.3% girls) from the Copenhagen Child Cohort (CCC2000) completed web-based questionnaires on eating behaviours and body dissatisfaction using The Eating Pattern Inventory for Children (EPI-C) and The Children's Figure Rating Scale. Mental disorders were assessed using the online version of the Development and Well-Being Assessment (DAWBA) based on parental replies with final DSM-IV diagnoses determined by experienced child- and adolescent psychiatrists. Height and weight were measured at a face-to-face assessment. The results showed that restrained eating was significantly associated with overweight, body dissatisfaction and emotional disorders in both genders. Emotional eating showed similar associations with overweight and body dissatisfaction in both genders, but was only associated with mental disorders in girls. External eating was significantly associated with body dissatisfaction and neurodevelopmental disorders in both genders, but was only associated with overweight in girls. Our findings show that problematic eating behaviours can be identified in preadolescence, and co-exist with weight problems and mental disorders. Thus restrained, emotional and external eating was, in different ways, associated with overweight, body dissatisfaction and mental disorders. Our findings point to significant eating behaviours in preadolescence, which could constitute potential predictors of later eating disorder risk. Highlights: Problematic eating behaviours in preadolescence are associated with overweight, body dissatisfaction and mental disorders. Body dissatisfaction is an important concurrent factor of restrained eating. Nearly one fifth of the children with problematic eating behaviours meet the criteria for a contemporaneous DSM-IV disorder.